2018
DOI: 10.1007/s00705-018-3742-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and complete genome of a novel nepovirus from red clover

Abstract: During high throughput sequencing (HTS) of leaves from a symptomatic red clover plant, a new RNA virus, tentatively named red clover nepovirus A (RCNVA), was discovered. The complete genomic sequence was determined and characterized. Particularly noteworthy was that RCNVA shares high sequence identities in RNA1 with a group of phylogenetically related nepoviruses while homologies in the RNA2 segments are markedly lower. Based on the genomic organization and phylogenetic attributes, RCNVA should be classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…) recently identified the genome of RCCV1 and found that its capsid protein sequence is closely related to its homolog from RCVMV but the RdRp sequence differs significantly. RCNVA is a new virus that was identified in red clover (Trifolium pratense L.) in the Czech Republic (Koloniuk et al, 2018). It was detected only once in 2018 in the sL pool of Landkreis Rostock.…”
Section: Viruses In the Surrounding Plantsmentioning
confidence: 99%
“…) recently identified the genome of RCCV1 and found that its capsid protein sequence is closely related to its homolog from RCVMV but the RdRp sequence differs significantly. RCNVA is a new virus that was identified in red clover (Trifolium pratense L.) in the Czech Republic (Koloniuk et al, 2018). It was detected only once in 2018 in the sL pool of Landkreis Rostock.…”
Section: Viruses In the Surrounding Plantsmentioning
confidence: 99%
“…A considerable disadvantage of growing clover is its limited persistence, due in large measure to its susceptibility to viral and phytoplasma diseases (Edwardson & Christie, ; Taylor & Quesenberry, ; Fránová et al , ; Jones, ). More than 30 viruses are known to infect red clover (Edwardson & Christie, ), and this list could certainly be extended with further discoveries (Fránová et al , ; Fránová & Jakešová, ; Koloniuk & Fránová, ; Lenz et al , ; Koloniuk et al , ,).…”
Section: Introductionmentioning
confidence: 99%
“…( Table 1 ) [ 14 , 26 , 27 , 28 , 29 , 30 ]. Red clover nepovirus A (RCNVA, genus Nepovirus ), red clover-associated varicosavirus ( Rhabdoviridae family), and phasey bean mild yellows virus (PBMYV, genus Polerovirus ) are suggested as new clover pathogens still pending official classification [ 31 , 32 , 33 ].…”
Section: Viruses Infecting Major Legumesmentioning
confidence: 99%
“…PSbMV, CMV, PEMV, PeSV, and BYMV cause mosaic and mottling, which is often confused with abiotic diseases (e.g., nutrient deficiencies, physiological disorders, herbicide damage, and waterlogging stress) [ 2 , 5 , 7 , 82 , 84 ]. The new but not officially approved polerovirus PBMYV [ 32 ] may also infect lentil.…”
Section: Viruses Infecting Major Legumesmentioning
confidence: 99%